ACADEMIC TRAINING OF NURSES AND THEIR IMPACTS ON PROFESSIONAL PRACTICE: A STUDY AT A PRIVATE UNIVERSITY IN RECIFE - PERNAMBUCO - Silva Meireles Suzano, Iracema; Pereira da Silva, Flávio (Health and Society, 2023)
Nurses are professionals of great importance to health services, because they are those who work in the management of the nursing team and thus, in the management of the care provided. Academic training, in turn, is the key to a good future performance of these health professionals. Thus, the objective of this study was to analyze the academic training of nurses in a private university in Recife and their impacts on professional performance. To obtain the data, an interview was conducted, based on a semi-structured questionnaire, in order to know the interviewees’ opinion about the questions proposed in the conversation. The instrument for data collection (questionnaire) presented closed and open questions, as well as information from the participants. The interview was conducted with 63 private college students. From the analyses, it was seen that the reality of the academic education of the nursing professional has changed radically in recent decades, because to maintain the rhythm of current clinical practice compared to the traditional, the “new” nursing professionals should have more knowledge about certain areas of work, meeting a social and health demand of the population. Thus, there is a need for an active teaching that has meaning for the student’s life, as well as some changes and greater knowledge about the documents that govern education in general. The analyses presented serve as a subsidy for other studies in education, health and the like.